Summary of the best evidence for stress ulcer prophylaxis in critically ill patients - Jin Wang; Xiaoxia Tang; Linhui Jin; Yunxia Shen; Jiang Zhang; Jixiong Shi; Ting Yin; Guilan Zhang; Hailin Zhu (Frontiers in Medicine, 2026)
Objective To gather, assess, and integrate the most reliable evidence regarding stress ulcer prevention in critically ill individuals, thus offering guidance for clinical application. Methods A comprehensive search was performed across various Chinese and English platforms and databases, such as UpToDate, National Guideline Clearinghouse (NGC), Registered Nurses' Association of Ontario (RNAO), Cumulative Index to Nursing and Allied Health Literature (CINAHL), Guidelines International Network (GIN), Eastern Association for the Surgery of Trauma (EAST), the Cochrane Library, PubMed, Web of Science, CNKI, Wangfang, VIP, Sinomed, the Full-text Database of Chinese Medical Journals, and Medlive. This search encompassed clinical decision-making tools, guidelines, systematic reviews, evidence summaries, expert consensus documents, randomized controlled trials (RCTs), and cohort studies. Additionally, a search for gray literature was carried out using Opengrey and DANS. The timeframe for the search extended from the establishment of each database up to April 14, 2026. Two researchers carried out independent assessments of literature quality, evidence extraction, and synthesis. Results In total, 29 publications were analyzed, which included 1 clinical decision document, 6 guidelines, 4 expert consensus statements, 2 systematic reviews, 13 meta-analyses, 2 cohort studies, and 1 randomized controlled trial (RCT). Ultimately, 32 key evidence statements were compiled across seven categories: risk factors, indications for prophylaxis and decision-making, selection of agents and methods of administration, integrated decision-making concerning enteral nutrition and stress ulcer prophylaxis (SUP), possible harms and adverse events, diagnosis and monitoring, as well as special populations and scenarios. In summary, this research consolidates the most reliable information regarding the prevention of stress ulcers (SUs) in patients with critical illnesses. Healthcare providers can utilize this evidence in a tailored way, taking into account the specific clinical situation and the preferences of the patient. The results offer a solid evidence-based framework for standardizing clinical approaches and enhancing patient outcomes. Systematic review registration The systematic review can be found at http://ebn.nursing.fudan.edu.cn/home , and its registration number is “ES202610400.”